(untitled) (PANGEEA, 2025)
ABSTRACT. Presentation, layout and tourism recovery of protected areas. Case Study - Detunata Goală geological protected area. "Abrud Country", the area where geological protected area Detunata is empty, has significant tourist resources, but the economic development almost exclusively on mining and quarrying. Restructuring of mining has led to a large number of unemployed, which is the only alternative: development and exploitation of touristic potential area. Most of the attractions is the geological protected area Detunata empty. This is a volcanic basalt neck columns formed by flaring the top. The paper presents a development project of this geological reservation. Key words: geological protected area, touristic potential area, basalt, neck.